Upregulation of the plant protein remorin correlates with dehiscence and cell maturation: A link with the maturation of plasmodesmata? - Raffaele, Sylvain (Landes Bioscience, 2009)
Remorins are plant-specific proteins found associated with plasma membrane microdomains, called lipid rafts. Recently, we have shown that this lipid raft marker also accumulated at plasmodesmata, likely within the plasma membrane lining these structures. Here, we have investigated the gene expression and protein accumulation patterns of remorin at the organ and cell type levels. We show that remorin level is significantly increased in dehiscent, mature and ageing tissues, as well as in source parts of the leaves, where mature branched plasmodesmata are in majority. these results suggest that remorin predominantly associates with mature branched plasmodesmata.